Hipersemiotika Bahaasa Operasional Matematika dalam Meme di Media Sosial - Mardiana, Ninik; Hatip, Ahmad (Jurnal Ilmiah FONEMA : Jurnal Edukasi Bahasa dan Sastra Indonesia, 2016)
Cyberspace or intenet meme overflowing with a diverse redership. The meme of the many very interesting to study memes containing operational language of mathematics. This is because the field of mathematics has a stereotype â€œhard and scaryâ€ for the learners. Therefore, the formulation of the problem in this research that is how forms, meaning, and function of mathematics meme that spread on the internet. With qualitative method, data sourcer ant with the use of 18 meme hipersemiotika approach, wil be divulged forms, meaning, and function of mathematics meme that exist in cyberspace. The result were obtained: (1) forms meme that imply about mathematics can be shaped mathematical facts, conceps of mathematics; (2) the meaning caontainde in memes are very waited and inculed content, images, and mathematical symbols and interconnected into a single entity that is mually in addition to helping student to bel able to recall math facts with ease as well as to insinuate, joke, and entertainment to is readers